Islamic Civic Ethics and Democratic Society: Exploring the Role of Shura, Justice, and Amar Maʿruf Nahi Munkar - Agus Suryana; Farhan Hari nugroho; Sumarta Sumarta (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2025)
Civic ethics in the context of a democratic state constitutes a crucial aspect that integrates Islamic values with the principles of modern democracy. This study aims to examine how Islamic values—such as shura (consultation), justice, and amar maʿruf nahi munkar (enjoining good and forbidding wrong)—can be implemented in civic practices that support democracy. Employing a qualitative, library-based research approach, this study analyzes relevant literature addressing the relationship between Islam, political ethics, and democracy. The findings indicate that Islamic-based civic ethics can strengthen democracy through civic education, character formation, and the application of shura in public decision-making processes. However, challenges such as ideological polarization and misinterpretation of Islamic values often hinder such implementation. The study recommends strengthening civic education grounded in Islamic values to foster an inclusive and ethical democratic society.